The Impact of International Financial Reporting Standards (IFRS) on Iranian Tax System - Ahmad Nasseri; Mehdi Mokhtari; Hamid Zarei (پژوهش‌های تجربی حسابداری, 2017)
The purpose of current paper is to consider the impact of adopting International Financial Reporting Standards on the efficiency of tax systems from the perspective of accounting and tax professionals in South Khorasan. To achieve intended goal in this study, descriptive method with the correlational approach has been used. The sampling method is based on classification and data gathered from a self-made questionnaire (after estimating the reliability and validity). The questionnaire is distributed among accounting professors of the university, members of the Iranian society of CPAs, managers and employees of taxation affairs organization in South Khorasan province. After completing the questionnaire, the statistical coefficients depending on the type of hypotheses (correlation coefficient, independent t-test, ANOVA, multivariate regression analysis) were calculated and analyzed using SPSS software. The results of hypotheses indicate that the use of International Financial Reporting Standards particularly standard No. 12. the income tax has a positive and significant impact to increase the efficiency of tax systems. The results can be used in line with adjusted accounting standards for more accommodating financial reports in terms of alignment with the needs of tax authorities. Therefore, the tax authorities can achieve an efficient tax system.